Preliminary study shows novel variant detected in the screening of RET gene in Malaysian patients with Hirschsprung’s disease - Nor Azian Abdul Murad; Then, Sue-Mian; Mohd Ridhwan Abd Razak; Conjeevaram Rajendrarao Thambidorai; Sri Noraima Othman; Rosniza Mohamad Hussain; Mohan Nallusamy; Syed Zulkifli Syed Zakaria; Isa Mohammad Rose; Zarina Latiff; Rahman Jamal (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Hirschsprung’s disease (HSCR) is a disorder associated with congenital absence of ganglion cells in the gastrointestinal tract. Molecular analyses have identified variants in various genes including RET, GDNF, EDN3 and EDNRB that are involved in the development, migration and survival of neural cells. Variants in the receptor tyrosine kinase (RET) are most common and have been identified in 10-20% of sporadic HSCR patients. The objective of this study was to screen for RET gene variants in Malaysian patients with HSCR. Thirty-two patients with HSCR and 30 normal controls were recruited for this study. Mutations were screened using the Polymerase Chain Reaction – Denaturing High Performance Liquid Chromatography (PCR-dHPLC) approach. Mutations identified were then confirmed using Sanger sequencing. We identified one novel rare variant in exon 4 (A268A c807 G>C) in one patient. We also identified the common coding sequence variantsA45A (c135G>A), A432A (c1296A>G), L769L (c2307 T>G) and the G691S in our cohort of patients. In conclusion, our Malaysian patients with HSCR diseases showed the presence of similar RET gene common variants which have been described in other populations. We have also identified a novel variant in exon 4 (A268A).